Health Care Facilities Mapping And Database Creation Using GIS In Chikun Local Government, Kaduna State, Nigeria (Global Journal of Human-Social Science, 2012)
The study investigated the spatial distribution of health care centres in Chikun local government area of Kaduna state, Nigeria with a view to use Geographic Information Systems (GIS) technique in health care management planning. The study used the administrative map of the study area collected from the local government as the base map. Information on the number and addresses of the health care centres in the study area were collected from the local government while the coordinates of the health care centres were obtained in the field using Global Positioning System (GPS). These data were incorporated into GIS environment and analysed using Arc Map 9.2 software.
Keywords: Health care; Centres; GIS; Mapping; Database